2012
DOI: 10.1016/j.immuni.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Respiratory Capacity Is a Critical Regulator of CD8+ T Cell Memory Development

Abstract: Summary CD8+ T cells undergo major metabolic changes upon activation, but how metabolism influences the establishment of long-lived memory T (TM) cells after infection remains a key question. We have shown here that CD8+ TM cells, but not effector CD8+ (TE) cells, possessed substantial mitochondrial spare respiratory capacity (SRC). SRC is the extra capacity available in cells to produce energy in response to increased stress or work and as such is associated with cellular survival. We found that interleukin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

69
1,308
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,261 publications
(1,415 citation statements)
references
References 49 publications
69
1,308
4
3
Order By: Relevance
“…Possibly it executes this role by bringing Dap10 into the IL-15 signaling complex, as was previously suggested (11). Interestingly, IL-15 was recently shown to mediate transition from glycolytic to oxidative metabolism during memory differentiation by inducing mitochondrial biogenesis (35). Thus, a model appears in which the NKG2D/IL-15R axis facilitates the transition from effector to memory stage.…”
Section: Discussionmentioning
confidence: 66%
“…Possibly it executes this role by bringing Dap10 into the IL-15 signaling complex, as was previously suggested (11). Interestingly, IL-15 was recently shown to mediate transition from glycolytic to oxidative metabolism during memory differentiation by inducing mitochondrial biogenesis (35). Thus, a model appears in which the NKG2D/IL-15R axis facilitates the transition from effector to memory stage.…”
Section: Discussionmentioning
confidence: 66%
“…Cytokines IL-2 and IL-15 are critical for the development and maintenance of CD8 + effector and memory T cells, respectively (36). To understand upstream and downstream mechanisms underlying Tsc1-dependent memory T-cell differentiation, we used an in vitro culture system that mimics the programs of effector and memory T-cell differentiation (13,37) and examined the effect of acute deletion of Tsc1 in this system. To this end, we crossed Tsc1 fl/fl with Rosa26-Cre-ER T2 (CreER) and OT-I transgenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging studies indicate that distinct metabolic pathways contribute to the fate decisions of effector and memory T cells. For instance, the increased glycolytic metabolism promotes effector T-cell generation (11), whereas oxidative phosphorylation and mitochondrial spare respiratory capacity facilitate memory T-cell differentiation (12,13). Recent studies have also identified transcriptional regulators of cell metabolism that promote effector T-cell differentiation, including HIF1 and IRF4 (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…6C), die because they cannot sustain their bioenergetic needs. Because memory T cells generally rely on oxidative phosphorylation for their bioenergetic requirements compared with effector cells, which primarily use glycolysis (45,46), a reduced mitochondrial mass and, thus, lower mitochondrial spare respiratory capacity in CD27-generated memory cells, could lead to their rapid demise.…”
Section: Discussionmentioning
confidence: 99%